Effect Of Price Sensitivity And Green Knowledge On The Interest In Buying Organik Vegetables In Bengkulu Province - Hilda Meisya Arif; Reflis Reflis; Andi Irawan; Indra Cahyadinata; Zulkarnain Yuliarso (UNIVED Press, Dehasen University Bengkulu, 2022)
Organic agricultural products in the current era are very attractive to farmers and consumers because there is no use of synthetic chemicals that can pose a danger to the health of the human body and the environment. Awareness of a healthy lifestyle makes the demand for organicproducts increasing for most consumers. Prices that are too high will make consumers switch to other similar products but with lower price offers make consumers doubt the quality of the product, thereby reducing buying interest in the product. . Green knowledge is defined as the knowledge that an individual has about knowing an issue or phenomenon that has a significant impact on the decision-making process. The purpose of this study was to determine the effect of price sensitivity and Green knowledge on the interest of organik sayuaran buyers in Bengkulu Province. This study was an associative study, using a sample of 100 respondents. Testing the research hypothesis using multiple regression, previously the data obtained must pass the validity and reability test. The results of the study stated that the variables of price sensitivity and green knowledge partially had an influence on the interest in buying organic vegetables in Bengkulu Province. Meanwhile, price and green knowledge together affect consumers' buying interest in organic vegetables. The value of the research determinant coefficient is 0.345, which means that the independent variable used only affects 34.5% of the variables tied to buying interest, while the remaining 65.5% is influenced by other variables outside the study.